Hyperpolarised xenon magnetic resonance spectroscopy for the longitudinal assessment of changes in gas diffusion in IPF. Issue 5 (2nd November 2018) - Weatherley, Nicholas D; Stewart, Neil J; Chan, Ho-Fung; Austin, Matthew; Smith, Laurie J; Collier, Guilhem; Rao, Madhwesha; Marshall, Helen; Norquay, Graham; Renshaw, Stephen A; Bianchi, Stephen Mark; Wild, Jim M
Abstract : Prognosticating idiopathic pulmonary fibrosis (IPF) is challenging, in part due to a lack of sensitive biomarkers. A recent article in Thorax described how hyperpolarised xenon magnetic resonance spectroscopy may quantify regional gas exchange in IPF lungs. In a population of patients with IPF, we find that the xenon signal from red blood cells diminishes relative to the tissue/plasma signal over a 12-month time period, even when the diffusion factor for carbon monoxide is static over the same time period. We conclude that hyperpolarised 129 Xe MR spectroscopy may be sensitive to short-term changes in interstitial gas diffusion in IPF.